Unifikasi Kalender Rasydhul Qiblah Harian Wilayah Sumatera Barat - Sakirman Sakirman (Islamic Astronomy Department, Sharia and Law Faculty, 2023)
Part of one of the obligatory conditions that must be fulfilled when Muslims perform the prayer service is facing the face and all members of the body towards the Qibla. The main problem with Qibla's direction is the long distance between the Kaaba and the mosque as a place of worship for Muslims. West Sumatra is an area thick with religious nuances, there are many mosques as places of worship for Muslims. So, the Qibla direction of the mosque must be accurate with the Kaaba. One method that can be used is to use the sun's shadow reflected by an object. The utilization of sunlight in determining the Qibla direction with this model is known as Rashdul Qiblah. This paper examines the importance of the unification of the Rasydhul Qiblah calendar with the central point of the district capital and the center of the regional capital of West Sumatra. The validity of the rashdul qiblah calendar at the center of the regency capital in the West Sumatra region can be used by the districts within it. This type of research is field research using a descriptive-analytical model. The results of a study of areas located in the center of the district capital of West Sumatra show that the timing of the implementation of the rashdul qiblah for the districts covering the center of the district capital has a time difference that can still be tolerated.